Sistem Rekomendasi Dosen Pembimbing Tugas Akhir Menggunakan Content Based Filtering - Anis Budiono; Sri Eniyati (STEKOM PRESS, 2023)
In general, the determination of supervisors at a university is determined by the department. The determination of supervisors is more on random factors or students who determine lecturers without considering the lecturers' expertise in the research to be carried out. The procedure for determining supervisors in this way will cause problems such as less than optimal results of the final assignment because the supervisor is not exactly selected. The final task supervisor has an important role because it has the responsibility to ensure that students are able to prepare the final assignment properly so that the final assignment is ready to be tested and qualified. In an effort to overcome the problem of inaccurate selection of supervisors, recommendations can be made based on expertise or research that has been carried out by supervisors using the con tent - based filtering method.